Brainstem Tuberculoma in Pregnancy - Dana A. Muin; Katrin Wagner; Rosemarie Burian; Naghmeh Ghaem Maghami; Olav Lapaire (Hindawi Limited, 2015)
We report a case of a Somali refugee who presented in the second trimester of her first pregnancy with a four-week history of gradual right-sided sensomotoric hemisyndrome including facial palsy and left-sided paresis of the oculomotorius nerve causing drooping of the left eyelid and double vision. Cranial magnetic resonance imaging revealed a solitary brainstem lesion. Upon detection of hilar lymphadenopathy on chest X-ray (CXR), the diagnosis of disseminated tuberculosis with involvement of the central nervous system was confirmed by PCR and treatment induced with rifampicin, isoniazid, pyrazinamide, and ethambutol. The patient had a steady neurological improvement and a favorable pregnancy outcome.